2013
DOI: 10.1007/s13365-013-0184-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise is associated with less neurocognitive impairment among HIV-infected adults

Abstract: Neurocognitive impairment (NCI) remains prevalent in HIV-infection. Randomized trials have shown that physical exercise improves NCI in non HIV-infected adults, but data on HIV-infected populations is limited. Community-dwelling HIV-infected participants (n=335) completed a comprehensive neurocognitive battery that was utilized to define both global and domain-specific NCI. Participants were divided into “Exercise” (n=83) and “No Exercise” (n=252) groups based on whether they self-reported engaging in any acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
48
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 42 publications
9
48
1
1
Order By: Relevance
“…This finding is consistent with previous research documenting that inconsistent or no PA is associated with concurrent risk for NCI in HIV-infected adults [36,37]. As would be expected, HIV-infected persons had worse neurocognitive function overall.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with previous research documenting that inconsistent or no PA is associated with concurrent risk for NCI in HIV-infected adults [36,37]. As would be expected, HIV-infected persons had worse neurocognitive function overall.…”
Section: Discussionsupporting
confidence: 92%
“…The relatively limited research on PA and cognition among those living with HIV is consistent with what has been shown among HIV-uninfected adults; higher levels of PA are associated with decreased concurrent risk for NCI [36][37][38]. Moreover, work by our group among older adults living with HIV has shown that active lifestyles (including PA) are associated with better cognition and that PA is associated with better cognition and everyday functioning among older adults living with HIV [39,40].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Certainly, exercise interventions for Nigerian HIV-patients (18 years and above) improved markedly both pulmonary functions and alleviated respiratory and depressive symptoms [35]. Physical activity engagement and employment are linked to greater performance in neurocognitive tasks [36][37][38]. Cross-sectional studies have indicated that activity and active engagement in daily activities bolsters neurocognitive functioning [39].…”
mentioning
confidence: 99%